Between mārga and démarche: a course in emptiness & différance - Tan, K. Cohen (2010)
This thesis forwards a path-based hermeneutics as a middle path (Skt. madhyamā-pratipad) between Deconstruction and Mādhyamaka, in order to understand our existential relatedness without reference to Being. It does not attempt to do so by way of a comparative analysis, which I believe results inevitably in some form of reification of both in terms of their method. Rather, what I see as unique to both Deconstruction and Mādhyamaka is this very lack of method – hermeneutical or otherwise – hence underscoring the significance of this path (either as démarche or mārga) that demands our existential response. The method is the argument, and in working through the various linguistic, epistemological, and ontological assumptions we thus engage (as our response and responsibility at once) with our very conditions of possibility that make them impossible at the same time.